Mouvement et variation d'altitude de la zone d'ablation ouest (latitude moyenne 69°40´N) de l'Indlandsis du Groenland entre 1948 et 1959. - Bauer, A.; Ambach, W.; Schimpp, O. (Meddelelser om Grønland, 1968)
In this first of the four reports on research by the Coastal Glaciological Group of EGIG, the author gives an account of the general idea of glaciological researches in ablation zone and the chronology of work. The matter was to determine the velocity, the variation of altitude of the ablation zone, the distribution of ablation, the accuracy of the measurements and the flow of melting waters. The detailed study of the energy budget should allow to measure each component factor of ablation. Movement and front variations of Eqip sermia should possibly been measured. With A. BAUER as a leader these investigations where carried out by O. SCHIMPP (Glaciology) and W. AMBACH (energy budget) from May 10th to August 11th, 1959 in Camp IV-EGIG (69°39'58" N, 49°37'44" W, 1013 m) and along a westeast profile of 40 km at the mean latitude of 69°40' N. A triangulation along this profile through markers measured in 1948, 1949, 1950, 1952 and 1953 allowed to determine the horizontal movement in the ablation zone. The movement is lineary, increasing from 18 m/year at the west border to 80 m/year at the equilibrium line along a distance of too km. Geodetic levelling and connection with geometric levelling of the same markers permitted the determination of the altitude variation of the profile. This variation , which represents a diminution of 0,30 m/year of water, has a disputable accuracy: by the movement of the markers along a rough surface and by incertain ablation values which vary from year to year, the extrapolation of the altitude measured in 1959 back to those of the position in 1948 or 1952 is hazardous. Nevertheless, the sign and the order of magnitude are valuable in accordance with observations of the negative balance of the Greenland ice sheet. Complementary observations of the movements of the border moraine conclude this report. The front of the ice sheet, which carries this moraine, is advancing by 1,5 m/year, in spite of a regular thinning since 1912.